Experimental comparative study of the histotoxicity of poly(lactic-co-glycolic acid) copolymer and poly(lactic-co-glycolic acid)-poly(isoprene) blend - Kim,Jung Ho (2014)
Current treatments of craniosynostosis rely on the application of metal springs for cranial bone deviation. However, those metal springs demand a second surgical procedure for their removal. An attractive alternative would be the substitution of metal for bioresorbable polymers in the composition of the springs. The addition of poly(isoprene), PI, to poly(lactic-co-glycolic acid), PLGA, produces a polymeric blend with partial miscibility and distinct mechanical behavior that may benefit the patient recover. It is necessary to compare the histotoxicity of PLGA/PI to that presented by PLGA. In order to verify the histological behavior of the blend, 46 male Wistar rats (Rattus norvegicus, albino strain) underwent implantation of PLGA or PLGA/PI in the skull and were allocated into subgroups by timing of euthanasia (15, 30, 60, or 90 days). After euthanasia, the skull was removed and the histotoxicity was assessed histopathologically. The PLGA/PI blend showed greater histotoxicity in animals euthanized at 60 days, although in this period the histotoxicity of the PLGA/PI blend was similar to that of the PLGA copolymer at 15 days. Despite the instability of histological response, presented in different periods of observation, the results obtained in long-term show that the material has high potential for studies in craniosynostosis treatment.